Editor’ Introduction: Agency, Aspiration, and Social Transformation in Contemporary Asia - Asep Muhamad Iqbal (Journal of Asian Social Science Research, 2025)
Abstract This editorial introduction presents JASSR Vol. 7, No. 1 (2025) as a reflection on how people across contemporary Asia navigate change under pressure. Rather than treating acceleration, mobility, conflict, and digitalization as abstract regional trends, it foregrounds the everyday practices through which students, migrants, minority communities, language learners, and women educators make choices within unequal social conditions. The issue brings together studies on AI use among international students, informal railway settlements in the Philippines, the Naxalite conflict in India, Indonesia–Malaysia historical relations, Korean language learning among Indonesian students, and Afghan women teachers’ professional resilience. Taken together, these articles show that social transformation is shaped not only by states, markets, and institutions, but also by ordinary acts of learning, settlement, memory, solidarity, and aspiration.